New energy grid connection power control method based on predictive tuning performance and embedded system - Lu, Yonglin; Liu, Zhigang; Zhang, Mingming; Wang, Xinfu; Chen, Yongmei; Shang, Jingrui (Frontiers in Energy Research, 2023)
As technology continues to evolve, the use of energy is constantly changing. Nowadays, the power generation method of new energy (NE) grid connection becomes popular, because the NE grid connection is relatively clean, and the efficiency of NE grid connection is also good. However, there are still some problems in the power control of NE grid connection, which cannot be well regulated.Therefore, this paper studied a NE grid connection power control method based on predictive regulation performance and embedded systems, aiming to control the power of NE grid connection through predictive regulation performance and embedded systems. This article tested the predictive regulation performance and the energy conversion rate of the embedded system's NE grid connection.In the experiments, the energy conversion rate was between 60% and 70%, while the traditional NE grid connection rate was between 40% and 60%. The maximum power generation efficiency of NE grid connection with predictive regulation performance and embedded systems was 83%, while the maximum power generation efficiency of traditional NE grid connection was 68%. From these experimental results, it can be seen that predictive regulation performance and embedded systems have a good effect on NE grid connected power control.